PPV derivative/ZnO nanorods heterojunction: Fabrication, Characterization and Near-UV light sensor development. (October 2018) - Jemmeli, Dhouha; Belhaj, Marwa; Ben Salem, Balkis; Jaballah, Nejmeddine; Yatskiv, Roman; Dridi, Chérif; Grym, Jan; Majdoub, Mustapha
Graphical abstract: Highlights: We have fabricated a PPV-C6/ZnO NRs heterojunction by a simple and low cost method. We have studied the structural and optical properties of the heterojunction. I–V characteristics of EGa-In/Si/PPV-C6/ ZnO NRs /graphite devices were analyzed. Photoelectrical study shows a potential opportunity for UV light sensor development. Abstract: Poly(1, 4-phenylenevinylene) derivative (PPV-C6 ) based solution was spin-coated onto hydrothermally grown and vertically aligned ZnO nanorods (ZnO NRs).The morphological and the optical properties of the PPV-C6 /ZnO NRs hybrid heterojunction have been studied and shown a penetration of PPV-C6 into the interspaces between the ZnO NRs with enhanced excitonic dissociation. The current–voltage characteristics in dark and under 395 nm LED illumination have been analyzed. A short-circuit current Jsc of 4691.42 μA/cm 2, an open-circuit voltage Voc of 0.46 V giving rise to a responsivity of about 29.32 mA/W have been obtained for the illuminated graphite/PPV-C6/ZnO NRs/Si/EGa-In structure based near UV light sensor showing an enhanced responsivity by a factor of about 200 compared with bare ZnO NRs based one. We have succeeded in the development of low cost near-UV light sensors by simple low temperature hydrothermal method using eco-friendly, low cost and easily fabricated electrodes.